Register Pengolahan Batu Kapur di Kabupaten Kebumen: Kajian Sosiolinguistik - Nurjannah, Nurjannah (P3M POLITEKNIK NEGERI AMBON, 2024)
The use of limestone processing registers by speech communities in Kebumen Regency, Central Java shows symptoms of language variation. The register serves to support social interaction with fellow professions. The purpose of this research is to find out the register of limestone processing and describe the form or characteristics of the register used by workers in carrying out their activities. Data collection was carried out using the introspection method, namely the author as part of the speaker. Observations of limestone processing activities and interviews with workers were conducted to validate the data. The data that has been collected is analyzed with sociolinguistic theory in terms of its form. From the results of data analysis, it was found that the limestone processing register has distinctive terms that are only understood by fellow users. The nouns and verbs in the limestone processing register have uniqueness such as word formation in the form of onomatopoeia and sound changes. The vocabulary in this register has meanings and functions that are specifically related to limestone processing activities. Keywords: register, limestone processing, form, meaning